Oesophagogastrectomy using the end-to-end anastomosing stapler. - Fabri, B (1982)
The use of a mechanical instrument for accomplishing end-to-side oesophagogastrostomy is described. We report our experience with 30 consecutive patients undergoing oesophagogastrectomy--26 for malignant disease and four for benign peptic stricture. There were two immediate postoperative deaths. One patient developed a chylothorax and died six weeks after operation. The instrument failed to function satisfactorily on one occasion. There were no anastomotic leaks.